Teachers’ Classroom Management in SMK Telkom 2 Medan - Roy Dedi Ansarika Ginting (English Language Teaching Prima Journal (ELT), 2019)
Abstract This study was aimed to investigate teachers’ classroom management in teaching learning process. The research was done in SMK Telkom 2 Medan. The period of observing the teachers’ classroom management was a week. The research’s participants of this study were the teachers in SMK Telkom 2 Medan. The instruments used in this research was observation. Based on the data analysis in the research, researcher found that the classroom management used by the teachers in SMK Telkom 2 were the exact moment of the lesson in which the teacher starts teaching, the locations of special needs students during the class period, use of rewards-punishment for special needs students and other students, use of individualized care for special needs students and the degree of effective use of classroom period.